Evaluation of anti anxiety activity of Datura seeds in mice - Alka Tiwari, Alka Tiwari; Jagdish Rathi, Jagdish Rathi; Sandeep Kumar Dwivedi, Sandeep Kumar Dwivedi; Sanno, Sanno; Saurab Tripathi, Saurab Tripathi (International Journal of Indigenous Herbs and Drugs, 2018)
Objective: The aim of the present work was to evaluate the anti-anxiety activity of ethanolic extract of Datura stramonium (leaves). Methods: Elevated plus-maze apparatus were used for finding anti-anxiety activity of the ethanolic extract of Datura stramonium (leaves). Pre-treated animals were placed individually for 5 min in the maze. The number of entries into the open and closed arm, time spent in each arm and the number of entries in both the arms was noted. Results: The result showed that the ethanolic extract of leaves of Datura stramonium (100 and 200 mg/kg) and diazepam (1 mg/kg) induced significantly (P<0.01) increase in the occupancy in the open arm and showed a decrease preference for the closed arm entries. Conclusion: Administration of ethanolic extract of leaves of Datura stramonium (100 and 200 mg/kg) possessed significant antiaxiety effects as compared to control.